Penggunaan Media Benda Konkret terhadap Hasil Belajar Matematika Tema Kegemaran pada Kelas III SDN Pangkemiri I Tulangan Sidoarjo - Ria Indhirawati; Nur Fajrie; Sri Surachmi W (Journal on Education, 2023)
Theoretically, third grade elementary school students are still in the ability to think concretely and view everything as a whole. Meanwhile, based on observations of class III students at SDN Pangkemiri I Tulangan Sidoarjo, it shows that when teaching, the teacher does not use learning media so that students have difficulty understanding the material presented. The teacher is only guided by the package book and Student Worksheet (LKS) and the role of the teacher is more than that of the students. Data collection techniques carried out are through observation, tests, interviews and documentation. Subjects in the study amounted to 32 students / i. The results showed that the classical completeness of student learning outcomes increased in cycle II.